Synthesis and physicochemical properties of silica gels with small additives of aluminium and zirconium ions - Bondar, L.А. (Поверхность, 2002)
The method of synthesis of silica gels containing small additives of Al and Zr ions was developed. The porous structure of the synthesized Al,Zr-silica gels has been characterized by the adsorption method. It was found that simultaneous modification of silica gels by aluminium and zirconium ions lead to the formation of micro- and ultramicroporous samples in neutral media of precipitation. The parameters of porous structure of Al,Zr-silica gels are considerably dependent on the modified ions contents. A supposition was made that the formation of porous structure was caused by mutual stabilizing effect of Al and Zr additives on silica gel globules growth at sol-gel stages of synthesis. The nature of surface active sites of the modified silica gels was studied by the diffuse-reflectance IR-spectroscopy with the use of adsorption of deuteroacetonitrile.